COMPARING VITRECTOMY, SILICONE OIL ENDOTAMPONADE WITH/WITHOUT CYCLOPEXY TO TREAT CYCLODIALYSIS CLEFTS WITH SEVERE OCULAR TRAUMA - Wang, Anan (Retina, 2021)
Comparing the anatomical and functional outcomes of vitrectomy, silicone oil endotamponade without cyclopexy (VEWOC) and with cyclopexy (VEWC) in patients with traumatic cyclodialysis clefts and severe ocular comorbidities. METHODS: A total of 55 patients (55 eyes) with traumatic cyclodialysis clefts were divided into VEWOC and VEWC groups according to the surgery undergone. Besides the cyclodialysis clefts, all study eyes had one or more additional conditions caused by severe ocular trauma: cataract, lens dislocation, vitreous hemorrhage, retinal detachment, choroidal detachment, maculopathy, suprachoroidal hemorrhage, subretinal hemorrhage, or proliferative vitreoretinopathy. The minimum postoperative follow-up period for all patients was six months. The main measures of outcome were rate of successful anatomical repair, intraocular pressure, and best-corrected visual acuity. RESULTS: Both the VEWOC group (33 eyes) and the VEWC group (22 eyes) showed significant improvement in postoperative best-corrected visual acuity and intraocular pressure at the final follow-up. The groups had no significant differences in terms of anatomical success rates (VEWOC 29/33 vs. VEWC 20/22, P = 1.000), final best-corrected visual acuity (VEWOC 1.60 ± 0.76 [median Snellen acuity: counting fingers, range: light perception to 20/20] vs. VEWC 1.46 ± 0.66 [median Snellen acuity: 20/800, range: light perception to 20/32], P = 0.485), and final intraocular pressure (VEWOC 13.40 [8.20–17.80] vs. VEWC 11.40 [6.65–14.00] mmHg, P = 0.311). However, the intraocular pressure on postoperative Day 1 was significantly different between the groups (VEWOC 10.40 [6.40–14.60] vs. VEWC 6.40 [4.70–7.98] mmHg, P = 0.002). CONCLUSION: This study showed that both surgical approaches were equally effective in treating cyclodialysis clefts secondary to severe ocular trauma. Therefore, it may be unnecessary to perform cyclopexy in addition to the vitrectomy procedure in such cases.